Mineralogical Tracing of Metallurgical Results - The Sarcheshmeh Copper Mine Case - S. Banisi; H. R. Iran-Manesh; M. R. Shayestefar; H. Shekarchyan (Canadian Institute of Mining, Metallurgy and Petroleum, 2003)
"Flotation circuit of the Sarcheshmeh copper mine processes 41,000 t/d of ore at 0.9% Cu. Chalcopyrite and chalcocite are the main copper bearing minerals which are concentrated in three stages of roughing, cleaning and recleaning. Due to major changes in the reagent addition regime, make-up balls combination, and throughput to the primary mills an increase of 2.6% (from 87.2% to 89.8%) in the sulfide copper recovery was obtained during a period of six years. In order to investigate a rather large variation of monthly recovery (i.e., from 89.0 to 91.2%) of the plant after implementation of the changes, a study was undertaken to trace mineralogically possible causes of such a behavior. During a five-month period, monthly composite samples of feed and tailings of the flotation circuit were taken. At the first stage, the polished sample preparation method and the mineral counting procedure were optimized through a detailed study. Liberation degrees and types of locking of valuable minerals in both streams were determined in three size intervals of +75, +38 and –38 microns. It was found that for both recovery levels (i.e., 89% and 91.2%), there was no significant difference in the liberation degrees of valuable minerals in the flotation feed; the average liberation degree was 57.1% with a standard deviation of 3.1%. On the other hand, in the case of high recovery level (i.e., 91.2%) there was a reduction of 15% in the amount of free valuable minerals in the tailings stream. The highest reduction was found for the -38 micron size range in particular for chalcocite. It was concluded that compared to the grinding circuit the change in the flotation circuit had the significant effect on the plant recovery increase.INTRODUCTIONThe Sarcheshmeh copper ore body contains 1 billion tonnes averaging 0.90 % copper and 0.03 % molybdenum. It is located southeast of Iran and currently processes 41,000 t/d of ore. The concentrator has been in operation since 1982. Last year, the concentrator produced 130,000 tonnes of copper and 4,000 tonnes of molybednite concentrate. An expansion to the plant which will increase the throughput by 50% is under construction and will be effective in 2003.After three stages of crushing, the ore with a F80 of 12.7 mm is fed to 8 parallel ball mills in closed circuit with cyclones to produce a product 70% finer than 75 microns. The concentrate of the first stage of flotation is reground and the tailings constitute the main component of the plant final tailings. A concentrate with an average grade of 30.5% Cu is obtained after cleaning and re-cleaning stages. At the present time, the average sulfide copper recovery of the plant is 89.8% which varies depending on the operating conditions and ore type."